Argos: Internacionalización en un entorno de conflicto armado* (2019)
This case study illustrates how Argos achieved to become one of the largest cement and concrete suppliers of Latin America, in spite of the fact that some of its production facilities are located in armed conflict areas. For that reason, the company implemented various corporate social responsibility strategies to overcome the difficulties of operating in these areas. These strategies contributed to the consolidation of the company’s operations under a single juridical and administrative entity, and facilitated the internationalization process to Central America, the Caribbean and the United States.